Data standards in healthcare supply chain operations (2011)
This paper presents the challenges and benefits associated with adoption of healthcare supply chain data standards in a hospital environment. In a highly fragmented industry like healthcare with several stakeholders, the adoption and use of common data standards for identifying delivery locations and products is critical. Common data standards ensure system wide interoperability and visibility across the supply chain, contributing to improvements in patient safety and streamlined internal and external supply chain operations. However, the global healthcare industry has been significantly slow in adopting data standards in comparison to other industries like retail, manufacturing. We discuss the results from data standard adoption pilot project conducted by Center for Innovation in Healthcare Logistics (CIHL), University of Arkansas at Washington Regional Medical Center, a 325 bed not-for-profit hospital in Fayet-teville, Arkansas. CIHL data standards pilot involved studying the existing supply chain processes, design, pilot-test, and evaluation of GS1 data standards adoption over a sample of products and a single delivery location at the hospital. We present the results, which demonstrate the capabilities of systemwide improvements and roadblocks likely to be encountered. Findings from the pilot can be expanded to develop a broad implementation plan of data standards adoption for healthcare providers.